2013
DOI: 10.1371/journal.pone.0075745
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid Beta Inhibits Olfactory Bulb Activity and the Ability to Smell

Abstract: Early olfactory dysfunction has been consistently reported in both Alzheimer’s disease (AD) and in transgenic mice that reproduce some features of this disease. In AD transgenic mice, alteration in olfaction has been associated with increased levels of soluble amyloid beta protein (Aβ) as well as with alterations in the oscillatory network activity recorded in the olfactory bulb (OB) and in the piriform cortex. However, since AD is a multifactorial disease and transgenic mice suffer a variety of adaptive chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 117 publications
5
36
0
1
Order By: Relevance
“…Our finding that A β inhibits PFC spontaneous network activity is very similar to observations by our group and others that direct application of A β inhibits spontaneous network activity in a variety of networks including the olfactory bulb [43], the entorhinal cortex [44], and the hippocampus [37, 45]. In fact, a previous finding already indicated that direct application of A β inhibits synchronized activity induced by calcium depletion in PFC slices [46].…”
Section: Discussionsupporting
confidence: 91%
“…Our finding that A β inhibits PFC spontaneous network activity is very similar to observations by our group and others that direct application of A β inhibits spontaneous network activity in a variety of networks including the olfactory bulb [43], the entorhinal cortex [44], and the hippocampus [37, 45]. In fact, a previous finding already indicated that direct application of A β inhibits synchronized activity induced by calcium depletion in PFC slices [46].…”
Section: Discussionsupporting
confidence: 91%
“…Aβ oligomers have a major role in the neurotoxic pathology of AD. A strong correlation also has been suggested between the accumulation of soluble Aβ in the OB and very early olfactory (including OB activity) dysfunction in both AD patients and transgenic mice [1,29]. Conversely, a reduced level of Aβ ameliorated the olfactory dysfunction observed in AD transgenic mice [27].…”
Section: Discussionmentioning
confidence: 99%
“…It is worth mentioning that research involving mice has shown that amyloid accumulating in the olfactory bulb inhibits its electrical activity, which oscillation amplitude is proportional to the smell task difficulty level [45]. In humans, olfactory bulb is a region, wherein occurs one of the earliest neuropathological alterations due to AD and its damage is common in this disease.…”
Section: Deterioration Of Olfactory Ability Over the Course Of Alzheimentioning
confidence: 99%
“…Warto wspomnieć, że badania na myszach wykazują, iż kumulujący się w opuszce węchowej amyloid hamuje jej aktywność elektryczną, której amplituda oscylacji jest wprost proporcjonalna do trudności zadania węchowe-go [45]. U ludzi opuszka węchowa jest rejonem, gdzie pojawiają się jedne z najwcześniejszych zmian neuropatologicznych związanych z AD; jej uszkodzenie jest powszechne w tej chorobie.…”
Section: Relationship Between Olfactory Ability and Cognitive Functionunclassified